Disseminated Cryptococcosis in an HIV-negative patient in South Africa: the elusive differential diagnosis - Mohammed Mitha; Preneshni Naicker; Prakash Mahida (Journal of Infection in Developing Countries)
The presence of an opportunistic infection in a patient in sub-Saharan Africa is assumed to be due to underlying immunosuppression from human immunodeficiency virus (HIV) infection. The presence of disseminated cryptococcosis in a non-HIV-infected patient is interesting as it is unique in our setting because the majority of infections are found in HIV-infected individuals. The protean manifestations of the disease and its predilection for immunosuppressed patients make cryptococcosis a challenging and elusive disease to diagnose in HIV-negative patients in our setting, especially due to limited resources. We present a case of disseminated cryptococcosis in an immunocompetent patient and discuss diagnostic and therapeutic features in this subset of patients.